On-Demand Drug Delivery: Recent Advances in Cardiovascular Applications - Genç, Hatice; Efthimiadou, Eleni; Cicha, Iwona (Frontiers in Drug Delivery, 2022)
Cardiovascular diseases (CVD), including life-threatening atherosclerosis and arterial thrombosis, account for almost 50% of all deaths in Europe and around 30% of all deaths worldwide. Despite the ongoing improvement and accessibility of invasive cardiovascular interventions and pharmacological therapies, pathological processes often progress asymptomatically, before manifesting themselves as unstable angina pectoris, myocardial infarction, sudden cardiac death or stroke. Since atherosclerosis and thrombosis represent localized disease processes, insufficient response to systemically-administered drugs is a common problem. The available pharmacological therapies are often burdened by poor tolerability, limited efficacy and/or bioavailability. Although encapsulating drugs in a nanoscale shell increases their circulation time and availability, it does not guarantee disease-specific targeting, or the proper control of the drug release. In contrast, on-demand drug delivery has the advantage of localized treatment and allows reducing off-target effects by a stimuli-controlled drug release in the affected region. Such “smart” systems are expected to have a great therapeutic potential in CVD. This mini-review article highlights recent advances in stimuli-responsive drug delivery approaches to CVD, with specific drug release triggered either internally or externally.